Thermodynamic assessment of the Fe–Sr–O system with special attention to the Perovskite phase. (16th January 2020) - Jantzen, Tatjana; Petersen, Stephan; Hack, Klaus
Highlights: Fe–Sr–O system thermodynamically assessed. Binary and ternary systems considered. Modified associate species model used for the liquid phase. Perovskite solid solution phase introduced using the multi-sublattice approach. Calculated phase diagrams and thermodynamic properties in good agreement with the experimental data. Abstract: In the present work a thermodynamic assessment for the Fe–Sr–O system is presented using all available experimental data on phase equilibria and thermodynamic properties. All sub-systems including elemental combinations were considered in order to generate a self-consistent Gibbs energy dataset for further calculation and prediction of thermodynamic properties of the system. The modified associate species model was used for the description of the liquid phase. Particular attention was given to the phase Perovskite SrFeO3−δ based on Brownmillerite SrFeO2.5 and extending significantly to higher amounts of oxygen, i.e. the SrFeO3 composition, according to the formula SrFeO3−δ . In addition to the component oxides five quasi-binary compounds located in the Fe2 O3 –SrO binary subsystem have also been included in the database as stoichiometric phases.